Effects of Pilates Exercises Versus Conventional Exercises Among Post-Menopausal Women Suffering From Non-Specific Low Back Pain, By Improving Lumbar Flexibility, Endurance, and Quality of Life – A Comparative Study (International Journal of Physiotherapy, 2025)
Background: Low back pain (LBP), or lumbago, is a major global public health issue, affecting up to 80% of people during their lifetime, with a peak incidence between 50 and 55 years of age. It is a leading cause of pain, functional limitations, and reduced quality of life. In India, nearly 60% of individuals report significant back pain. Most LBP cases are non-specific and idiopathic, making diagnosis and treatment challenging. Contributing factors include sedentary lifestyles, obesity, smoking, and physical strain.Methods: A 12-week intervention study involved 80 postmenopausal women with lumbago, randomly assigned to a Pilates group (n=40) or a conventional exercise group (n=40) after getting informed consent. Participants exercised three times per week. Outcomes were measured pre- and post-intervention using the Numeric Pain Rating Scale (NPRS), Oswestry Disability Index (ODI), Menopause-Specific Quality of Life (MENQOL) questionnaire, and the Kraus-Weber test.Results: Both groups showed significant improvements (p < 0.05), but the Pilates group had more significant reductions in pain (NPRS: mean difference = 3.42, p = 0.001), disability (ODI: 6.6 points, p = 0.002), and enhanced flexibility (8.63 points, p = 0.001). Lumbar flexion improved by 4.25° (p = 0.001) vs. 2.68° in controls, and extension/rotation improved significantly (p = 0.003). Quality of life (MENQOL) improved by 13.02 points (p = 0.001), and endurance (Kraus-Weber) by 2.37 points (p = 0.001) vs. 1.02 in the control group. Pilates enhanced lumbar mobility, strength, endurance, and overall quality of life in postmenopausal women with nonspecific low back pain.Conclusion: While both exercise methods benefit postmenopausal women with lumbago, Pilates was more effective in reducing pain and disability and improving flexibility and quality of life. A 12-week Pilates program is a beneficial, noninvasive approach for managing lumbago and enhancing physical function in postmenopausal women.Trial registration: Clinical Trials Registry- India (CTRI), CTRI/2024/04/065057. Registered on 02/04/2024.